Teacher Performance Management in Improving Learning Achievement of Elementary School Students - Ina Yuningsih; Ida Tejawiani (Papanda Publisher, 2026)
Suboptimal teacher performance management implementation contributes to persistent low student achievement in Indonesian elementary education, yet limited research examines how contextual variations shape management effectiveness in resource-constrained rural settings. This qualitative comparative case study investigated teacher performance management across Armstrong's five-stage framework (planning, implementation, monitoring, assessment, follow-up) at two elementary schools in Naringgul District, Cianjur Regency. Data were collected through in-depth interviews with principals, teachers, and students; participatory classroom observations; and document analysis, then analyzed using Miles, Huberman, and Saldaña's interactive model. Both schools implemented all performance management stages systematically, though with distinct approaches: SDN Mulyasari employed backward design planning and spontaneous differentiated instruction despite infrastructure limitations, achieving 65% student competency attainment, while SDN Tegallame utilized behavioral objectives planning and programmatic differentiation with superior technology integration, achieving 75% attainment. The study revealed effective monitoring requires